Ultrasonographic measurement of placental thickness and its correlation with estimated fetal weight - Noor, Nasreen; Jain, Akanksha; Parveen, Shazia; Ali, Syed Manazir (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The human placenta develops with the principal function of providing nutrients and oxygen to the fetus. Objective of present study was to assess the relationship between placental thickness with estimated fetal weight. Methods: The present study was a prospective observational study and includes 152 pregnant women with known last menstrual period, history of regular menstruation, singleton pregnancy and aged between 20 and 35 years. After Institutional Ethics Committee approval all recruited women were observed for baseline demographic and obstetric data including age, parity and past medical events at first antenatal visit. All women provided an informed written consent and underwent ultrasound evaluation of placental thickness at 18 to 40 weeks of gestation. Results: In the present study the mean placental thickness between the ranges of 18-40mm was 31.63±4.79mm and the mean estimated fetal birth weight was 2145.86±121.24grams. The pearson’s correlation coefficient between the two was 0.982. Thus, proving the significant positive correlation between placental thickness and estimated fetal birth weight (p-value <0.001). Conclusions: Estimated fetal weight is a very important component of antenatal care in which ultrasonography plays an important role. Placental thickness measured at the level of umblical cord insertion can be used as an accurate sonographic indicator in the assessment of fetal weight because of its linear correlation. Therefore, it can be used as an additional sonographic tool in assessing fetal weight.